Characterization of the circumferential cevel of the pulmonary vein isolation area using pulsed-field catheter ablation: Spatial distribution and extent of insufficient and excessive isolation areas. (19th May 2022) - Bohnen, M; Weber, R; Eichenlaub, M; Jadidi, A; Neumann, FJ; Arentz, T; Lehrmann, H
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: The cornerstone of pulmonary vein isolation (PVI) is a wide area circumferential ablation (WACA) resulting in an isolation area encompassing the PV antrum. Pulsed field ablation (PFA) is a new non-thermal "single-shot" PVI device with promising success rates. However, the circumferential level of its PV isolation area is still unknown. Objective: To characterize the circumferential acute PV isolation area by assessing the spatial distribution (qualitative analysis) and extent (quantitative analysis) of insufficient PV antral and excessive LA isolation areas. Methods: In this study, patients with paroxysmal or persistent atrial fibrillation (AF) underwent PVI with a pentaspline PFA catheter. Before and immediately after PVI, ultra-high-density (UHD) voltage maps using a 20-polar circular mapping catheter were created. The insufficient isolations areas per antral PV segment (10-segment model) and excessive isolation areas per LA region (8-region model) were quantified. Results: Between November – December 2021, in forty consecutive patients (age 62 ± 6 years, 28/40 [70%] male, LA 41 ± 4 mm) acute PVI using PFA was achieved and pre (5469 ± 1822 points) and post mapping (6809 ± 2769 points) was performed. The anterior antral PV segments of the left PVs were the most frequent locations of insufficient isolation areas (Table 1, Figure 1). The largest extent of insufficient isolation areas at the PV antral level was located again on the anterior parts of both left PVs (Figure 2A), but also in the anterior lower segment of the right inferior PV (Figure 2B). The posterior wall and roof region of both LA sides were the most frequent locations of excessive isolation areas (Figure 4). The extent of this excessive isolation at the roof and the posterior wall on both LA sides even resulted in a connection of the both-sided low voltage areas in 18% and 8%, respectively. Conclusion: When using PFA to achieve a circumferential antral PVI, efforts should be made to enhance anterior antral PV segment and prevent excessive posterior wall and roof ablation. For further optimizing the procedure, full integration of PFA catheter visualization into 3D-mapping systems is needed.